2012
DOI: 10.1001/archgenpsychiatry.2012.222
|View full text |Cite
|
Sign up to set email alerts
|

The Antisocial Brain: Psychopathy Matters

Abstract: Reduced GM volume within areas implicated in empathic processing, moral reasoning, and processing of prosocial emotions such as guilt and embarrassment may contribute to the profound abnormalities of social behavior observed in psychopathy. Evidence of robust structural brain differences between persistently violent men with and without psychopathy adds to the evidence that psychopathy represents a distinct phenotype. This knowledge may facilitate research into the etiology of persistent violent behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 129 publications
(194 reference statements)
6
109
3
2
Order By: Relevance
“…27 In previous studies, structural posterior cingulate cortex abnormalities were seen in children with callous unemotional traits 28 and some adults with psychopathy, 29 but these were not seen in the sample in this study. 7 Reduced posterior cingulate cortex responsivity to emotional stimuli, 30 including personal moral dilemmas, 31 has also been seen in investigations of adults with psychopathy. A white-matter diff usion tensor imaging study of the off enders with antisocial personality disorder and psychopathy from this study revealed reduced fractional anisotropy suggestive of reduced axonal integrity and organisation in the dorsal cingulum, which links the posterior cingulate cortex to the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…27 In previous studies, structural posterior cingulate cortex abnormalities were seen in children with callous unemotional traits 28 and some adults with psychopathy, 29 but these were not seen in the sample in this study. 7 Reduced posterior cingulate cortex responsivity to emotional stimuli, 30 including personal moral dilemmas, 31 has also been seen in investigations of adults with psychopathy. A white-matter diff usion tensor imaging study of the off enders with antisocial personality disorder and psychopathy from this study revealed reduced fractional anisotropy suggestive of reduced axonal integrity and organisation in the dorsal cingulum, which links the posterior cingulate cortex to the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 90%
“…34 Insular damage in human beings promotes risky decision-making because of impaired signalling of the probability of aversive outcomes. 35 Reductions in grey-matter volume in the insula have been reported in adults with psychopathy, 7,29 as have reductions in insula activity during aversive conditioning 30 and atypically increased activation in response to empathy-eliciting scenarios. 8 Regions involved in representing subjective value, such as the ventromedial prefrontal cortex and posterior cingulate cortex, have been proposed to integrate input from the superior temporal gyrus.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another avenue for developing research in the field is to examine G 9 E affecting endophenotypes in order to uncover the complex biological mechanisms underlying G 9 E. As discussed elsewhere in this volume, the endophenotypes related to human violence and their genetic risk variants involve structure and function of limbic and cortical regions such as amygdala, hippocampus, and medial prefrontal as well as cingulate cortex (Buckholtz and Meyer-Lindenberg 2008), plus anterior temporal and rostral prefrontal areas in antisocial offenders with psychopathy (Gregory et al 2012). Similar structural deviance is already evident in children and adolescents with conduct disorder (Huebner et al 2008) or callous-unemotional traits (Viding and McCrory 2012).…”
Section: Directions For Future Researchmentioning
confidence: 99%